2011
DOI: 10.1080/10426507.2011.597805
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on the PCP(O) Linear Moiety: How to Stabilize Diphosphaallenic Derivatives

Abstract: Density functional theory calculations on phosphavinylidene(oxo)phosphorane RP C P( O)R I are reported, where the R and R groups represent substituents with various . The investigations provide information about the groups that seem to be the best choice for the stabilization of such systems. The influence of the substituents' nature on the geometrical parameters and Wiberg bond orders for the P C bonds are discussed. Two isomers of I with a PCPO linkage (P≡C P( O)RR II and O P C≡PRR III) have also been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The molecular structures of model PCPX ligands were optimized at the DFT (PBE0/Def2-TZVP) level of theory, with their most relevant geometrical parameters being presented in Table S1. † It must be recalled that the structural properties of model compounds containing the P]C-P]O fragment have already been described in previous DFT studies by our group [23][24][25] and therefore, a detailed structural characterization of the PCPO models employed herein is beyond the purposes of the current study. However, theoretical data reported for derivatives incorporating the P]C-P]S moiety are scarce.…”
Section: Pcpx Model Derivativesmentioning
confidence: 99%
“…The molecular structures of model PCPX ligands were optimized at the DFT (PBE0/Def2-TZVP) level of theory, with their most relevant geometrical parameters being presented in Table S1. † It must be recalled that the structural properties of model compounds containing the P]C-P]O fragment have already been described in previous DFT studies by our group [23][24][25] and therefore, a detailed structural characterization of the PCPO models employed herein is beyond the purposes of the current study. However, theoretical data reported for derivatives incorporating the P]C-P]S moiety are scarce.…”
Section: Pcpx Model Derivativesmentioning
confidence: 99%
“…Concerning the lone pair electrons (LP) on the two P atoms, NBO calculations reveal a mixed s-p AO character in all cases (about 55-65% s and 45-35% p), as previously revealed in other theoretical studies. 14 In addition, the molecular structure of system 4 was investigated by DFT calculations, in order to assess the relative stability of the species with the P=S bond involving the sp 2 P atom related to the experimental observed derivative 3. Nonetheless, computed enthalpies indicate a higher stability for 3, with a calculated gap (∆H 3-4 ) of about 5 kcal mol -1 .…”
Section: In the Crystal Lattice Further Associations Through C-h•••clmentioning
confidence: 99%
“…A theoretical study revealed that the presence of bulky organic groups connected to the P(V) atom induce a stabilizing effect but their electronic effects also play an important role in the stabilization of such compounds. 14,15 For example the silyl group connected on the P(V) atom increases the stability of RP=C=P(=E)R derivatives. In contrast, the presence of electronwithdrawing groups leads to the decrease of the bond order in the -C=P(=E) fragment.…”
Section: Introduction *mentioning
confidence: 99%
“…An additionally study shows that the electronic effect is also important in the stabilization of such compounds. 9 For example the silyl group linked on the P(V) atom increase the stability of derivatives RP=C=P(=O)R, while the presence of electron-withdrawing groups destabilizes the diphosphaallenic systems.…”
Section: Introduction *mentioning
confidence: 99%